Catalytic mechanism of the colistin resistance protein MCR-1. Issue 17 (19th February 2021) - Suardíaz, Reynier; Lythell, Emily; Hinchliffe, Philip; van der Kamp, Marc; Spencer, James; Fey, Natalie; Mulholland, Adrian J.
Abstract : Elucidation of the catalytic reaction mechanism of MCR-1 enzyme, responsible for the antimicrobial resistance to colistin, using DFT calculations on cluster models. Abstract : The mcr-1 gene encodes a membrane-bound Zn 2+ -metalloenzyme, MCR-1, which catalyses phosphoethanolamine transfer onto bacterial lipid A, making bacteria resistant to colistin, a last-resort antibiotic. Mechanistic understanding of this process remains incomplete. Here, we investigate possible catalytic pathways using DFT and ab initio calculations on cluster models and identify a complete two-step reaction mechanism. The first step, formation of a covalent phosphointermediate via transfer of phosphoethanolamine from a membrane phospholipid donor to the acceptor Thr285, is rate-limiting and proceeds with a single Zn 2+ ion. The second step, transfer of the phosphoethanolamine group to lipid A, requires an additional Zn 2+ . The calculations suggest the involvement of the Zn 2+ orbitals directly in the reaction is limited, with the second Zn 2+ acting to bind incoming lipid A and direct phosphoethanolamine addition. The new level of mechanistic detail obtained here, which distinguishes these enzymes from other phosphotransferases, will aid in the development of inhibitors specific to MCR-1 and related bacterial phosphoethanolamine transferases.